Identification and mapping of multi-type flood hotspots using an ensemble technique in the transboundary of Kabul River Basin - Zahid Ur Rahman; Fang Chen; Meimei Zhang; Jiahua Zhang; Muhammad Hussain; Safi Ullah; Peyman Yariyan; Zahoor Ahmad (Journal of Hydrology: Regional Studies)
Study region: The Kabul River Basin (KRB), located in the eastern Hindukush region, is a transboundary basin shared by Afghanistan and Pakistan. Study focus: This study aims to identify and map hotspots for five major flood types: ephemeral, fluvial, flash, urban, and glacial lake outburst floods (GLOFs) using three models: the Frequency Ratio (FR), Expert Opinion-based Analytical Hierarchy Process (EO-AHP), and Prediction Rate-based Analytical Hierarchy Process (PR-AHP). By analyzing 620 flood locations and 18 flood predictors, we found that 14 %, 20 %, and 15 % of the study area derived from FR, EO-AHP, and PR-AHP models were highly susceptible to multi-type floods, respectively, highlighting susceptible hotspots of different floods in the KRB. New hydrological insights for the region: This study provides a comprehensive multi-type flood susceptibility map for the KRB. The findings of this study are crucial for effective flood management, as they identify and integrate multi-type floods into a single map. The study helps relevant authorities in prioritizing resource allocation, improving early warning systems, and implementing sustainable land use planning, ultimately improving flood preparedness and building resilience through risk-informed policy-making.